New method of surgical fixation of fracture of condylar process of mandible - Mehtiyev, O.; Jusubov, J.; Mammadov, J. (Actual Dentistry, 2018)
Summary. At last decades, the number of patients with traumatic injuries of maxillofacial region has increased significantly. Mandibular fractures are often seen during maxillofacial traumatic injuries. Condylus is a most fraqment fractured part in a mandible. Anatomic features of condylar processus are the cause of a number of difficult during the reposition an fixation of fractured fragments. In this article we are going to talk about the new method of fixation during mandibular condylar fractures. Key words: mandibular bone, condylar process, treatment.